El material didáctico como herramienta metodológica para mejorar el proceso de enseñanza - aprendizaje, en el área de ciencias naturales de los niños y niñas de quinto grado del subnivel básica media, de la escuela María Montessori de la parroquia Malacatos, cantón y provincia de Loja, período lectivo 2013 – 2014 - Guaman Sanchez, Kathy Liliana (2015)
This thesis carried on teaching materials as a methodological tool to enhance teaching-learning process in the area of natural sciences children in fifth grade of elementary and secondary school sublevel Maria Montessori Malacatos parish, county and province Loja, school year 2013-2014, the methods used to conduct the research were: analytic-synthetic, inductive-deductive and as techniques used: the surveys of 35 students and a teacher. Analysis and interpretation of results will then be proceeded, the same which revealed that the teacher uses the surrounding materials 100% because it has little material for teaching the subject of natural science, which I consider those circumstances are an excuse to rely on the use of one type of teaching material resulting in students difficulties in performing their tasks, boredom, concentration, sleep and disinterest in studying the subject, which is why four educational workshops each applied I use different types of teaching materials to provide meaningful learning demonstrated through the Pearson r. The use of consistent training material to each thematic study helps to activate prior knowledge, comprehend, understand, better knowledge and general academic performance is improved.